Mechanistic and spectroscopic investigations of Ru3+-catalyzed oxidative degradation of azidothymidine by heptavalent manganese at environmentally relevant pH - Kulkarni, Raviraj M.; Bhamare, Vijaykumar S.; Santhakumari, B. (Desalination and Water Treatment, 2016)
The rapid increase in the population across the world has increased the consumption of pharmaceutical substances. These pharmaceutical substances have penetrated into the water through various ways. Mechanistic and spectroscopic investigations of Ru3+-catalyzed oxidative degradation of azidothymidine (AZT) by heptavalent manganese was studied for the first time. The values of pH-dependent apparent second-order rate constant show that Ru3+ accelerates the rate of the oxidative degradation of AZT by heptavalent manganese eight times faster than uncatalyzed reaction. Ru3+ catalytic oxidative degradation of AZT by heptavalent manganese was greatly depending on the pH. The removal of the AZT by heptavalent manganese in the presence of Ru3+ shows unit order with respect to heptavalent manganese, Ru3+, and AZT. The influences of dielectric constant, ionic strength, pH, addition of monomer, variation in catalyst concentration, etc. on the rate of the reaction were studied thoroughly and discussed in detail. The eight different products produced during the reaction were analyzed using the high-resolution mass spectrometry. Activation parameters were determined from variation in temperature during the reaction. The catalytic plausible mechanism was projected in which Ru3+ is oxidized to higher oxidation states of ruthenium by heptavalent manganese at environmentally relevant pH.
Keywords: Azidothymidine; catalysis; Degradation; Heptavalent manganese; kinetics; Mechanism

Oxidation of linezolid by permanganate in acidic medium: Pd(II) catalysis, kinetics and pathways - Kulkarni, Raviraj M.; Hanagadakar, Manjunath S.; Malladi, Ramesh S.; Santhakumari, B.; Nandibewoor, Sharanappa T. (Progress in Reaction Kinetics and Mechanism, 2016)
The uncatalysed and Pd(II)-catalysed oxidation of linezolid (LNZ) by permanganate (PMGT) in acidic medium was carried out in the pH range from 3.0 to 6.0. The second order rate constants were found to decrease with increase in pH. The apparent second order rate constants for the uncatalysed reaction were, for example, k `'(app)= 6.32 dm(3) mol(-1) at pH 3.0 and k `'(app). = 2.64 dm(3) mol(-1) s(-1) at pH 6.0 and at 25 +/- 0.2 degrees C and for the Pd(II)-catalysed reaction the total apparent second order rate constants were k `'(app) = 75.5 dm(3) mol(-1) s(-1) at pH 3.0 and k `'(app). = 45.66 dm(3) mol(-1) s(-1) at pH 6.0 and at 25 +/- 0.2 degrees C. The rate constant of the Pd(II)-catalysed reaction was thus ten times higher than for the uncatalysed reaction. The oxidation products of the reaction were identified using high resolution LC-MS. The reaction progresses via formation of a Pd-LNZ complex, which reacts with acidic PMGT to form an intermediate compound, which then decomposes to give oxidised products. The dependence of the rate of reaction on various parameters, such as pH, temperature, [LNZ], [PMGT], [Pd(II)], dielectric constant and ionic strength were studied and activation parameters for the reaction were evaluated and discussed.

Oxidative transformation of antiretroviral drug zidovudine during water treatment with permanganate: reaction kinetics and pathways - Kulkarni, Raviraj M.; Bhamare, Vijaykumar S.; Santhakumari, B. (Desalination and Water Treatment, 2016)
The presence of the pharmaceutical substances in the water has been reported by many studies and has attracted attention across the world. The mechanistic insight into oxidation of antiretroviral drug zidovudine (ZDV) by potassium permanganate was investigated between the pH values 3.0 and 9.0. The pH-dependent second-order rate constants were determined and rate constants decreased with an increase in pH. The products of the reaction were identified by high-resolution mass spectrometry. A probable mechanism is proposed which involves the formation of an intermediate complex between permanganate and ZDV, which further undergoes degradation in subsequent fast steps to form various oxidized products. The different parameters like effect of initially added products, solvent polarity, ionic strength, temperature, and pH on the rate of the oxidative degradation of ZDV by permanganate were systematically studied. The various activation parameters were determined from the effect of variation in temperature on the oxidative degradation of ZDV by permanganate in acidic medium and discussed in detail.
Keywords: Degradation; kinetics; Mechanism; Permanganate; Zidovudine